Catalytic asymmetric [3 + 2]-cycloaddition for stereodivergent synthesis of chiral indolyl-pyrrolidines. Issue 5 (11th January 2016) - Arai, Takayoshi; Tokumitsu, Chihiro; Miyazaki, Tomoya; Kuwano, Satoru; Awata, Atsuko
Abstract : The stereochemical divergent synthesis of indolyl-pyrrolidines was accomplished using an imidazoline-aminophenol (IAP)–Ni(OAc)2 complex and a bis(imidazolidine)pyridine (PyBidine)–Cu(OTf)2 complex. Abstract : The stereochemical divergent synthesis of indolyl-pyrrolidines was accomplished using an imidazoline-aminophenol (IAP)–Ni(OAc)2 complex and a bis(imidazolidine)pyridine (PyBidine)–Cu(OTf)2 complex. The former catalyzed exo ′-selective asymmetric [3 + 2] cyclization of iminoesters with indolyl nitroalkenes, and the latter catalyzed the reaction in an endo -selective manner. These catalysts are tolerant toward highly functional substrates that supply chiral indolyl-pyrrolidine hybrids.